Culturally Adapted Motivational Interviewing for Latino Heavy Drinkers: Results from a Randomized Clinical Trial - Lee, Christina S. (2013)
A randomized clinical trial of culturally adapted (CAMI) and un-adapted motivational interviewing (MI) to reduce drinking and related problems among heavy drinking Latinos randomized and assessed 58 participants at baseline, at 2 (86% retention) and 6 months (84% retention). Significant declines across both were found in heavy drinking days/month and drinking consequences (p < .001), with greater reductions for drinking consequences for CAMI at 2 months (p = .009) and continuing reductions in CAMI at 6 months. Findings provide preliminary support for the value of culturally adaptation to enhance the efficacy of motivational interviewing with Latino heavy drinkers.